Prevalence of insufficient fruit and vegetable intake and associated factors in older adults in Thailand - Kanyapak Silarak (2021)
This cross-sectional study aimed to describe the prevalence of insufficient fruit and vegetable intake (FVI), and examined factors associated with insufficient FVI in adults aged 50 years and older in the communities of Thailand. The data collection was conducted from September 2015 to March 2016. Multi-stage cluster sampling was used to draw a sample of 3,875 in 16 districts from 14 provinces across different regions of Thailand. The variables were collected included socio-demographic factors, lifestyles, anthropometric factors, health status and FVI. An Electronic form was developed for data entering from all study sites. Face to face interview by trained research assistants was used to fill up the electronic form of questionnaire. Chi-square test and multiple logistic regression were performed to examine associations between the independent variables and insufficient FVI. From the total number of participants, 97.73% completed questionnaires. The majority (72.9%) were 50 to 69 years old. Overall prevalence of insufficient FVI were 77.4 %, 78.3 % among men and 76.9% among women. In multiple logistic regression, marital status, household monthly income, regions, and tobacco used (Adj OR = 1.36, 95% CI= 1.04-1.78) were significantly associated with insufficient FVI. After adjusting for other factors, older adults who used tobacco were 1.36 times more likely to have insufficient FVI than those who did not. The amount of fruit and vegetable intake by older adults in communities of Thailand were considerably lower than current recommendations (daily intake of at least five servings; 400 g). The results suggested that public education and campaigns on adequate consumption of fruit and vegetable should be promoted to target low household monthly income, north eastern region, and tobacco use. This findings could help health promotion policy implementation to increase FVI among this target group in Thailand.